Evaluating Frozen Strawberries as a Strategy for Thirst Management in Patients with Congestive Heart Failure (CHF) - Hudiyawati, Dian; Suswardany, D. L. (IIUM Medical Journal Malaysia, 2021)
INTRODUCTION: Thirst sensation in Congestive Heart Failure (CHF) patients is caused by diuretic administration and fluid consumption limitation. Unhandled thirst sensation leads to a disobedient patient in fluid consumption limitation that causes the patient condition to worsen. This research aimed to analyse the frozen strawberries administration's effects on the thirst sensation in a patient with CHF . MATERIAL AND METHOD: The method used was a quasi-experiment with a pre-test and post-test control group design. The number of respondents was 34 patients divided into two groups: 17 respondents in the intervention group and 17 respondents in the control group. The sampling technique was stratified random sampling based on NYHA classification in the respondents. Frozen strawberries were given to the intervention group, while ice cubes were given to the control group. All the data were analyzed using a t-test.RESULT:The results showed that the mean score of the thirst intensity of the intervention and control group was 4.44 and 2.35, respectively. The independent t-test of the mean difference of thirst intensity pre and post-test between the intervention and control groups was p=0.001. According to the paired t-test analysis, the thirst intensity score between pre-test and post-test was p<0.001, from moderate to low thirst intensity. CONCLUSION:Frozen strawberries were statistically effective in reducing the thirst intensity in a patient with CHF.